2021
DOI: 10.3389/fcell.2021.686453
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Mesenchymal Stem/Stromal Cell-Based Delivery: A Rapidly Evolving Strategy for Cancer Therapy

Abstract: Mesenchymal stem/stromal cell (MSC)-based therapy has become an attractive and advanced scientific research area in the context of cancer therapy. This interest is closely linked to the MSC-marked tropism for tumors, suggesting them as a rational and effective vehicle for drug delivery for both hematological and solid malignancies. Nonetheless, the therapeutic application of the MSCs in human tumors is still controversial because of the induction of several signaling pathways largely contributing to tumor prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 145 publications
(180 reference statements)
0
14
0
Order By: Relevance
“…The strong tumor tropism of MSCs makes them reliable candidates as gene delivery vehicles, providing sustained and continued releases of antitumor cytokine. Based on the recent reports, MSCs can unfavorably support tumor progress by a diversity of mechanisms, containing the stimulation of drug resistance, proangiogenic functions, and eliciting metastasis procedure by stimulation of epithelial-mesenchymal transition (EMT) and also enrichments of the cancer stem cell (CSC) niche (139,140). MSC-derived factors are reliable for the listed unwanted effects, affecting the various hallmarks of cancer.…”
Section: Conclusion and Future Prospectmentioning
confidence: 99%
“…The strong tumor tropism of MSCs makes them reliable candidates as gene delivery vehicles, providing sustained and continued releases of antitumor cytokine. Based on the recent reports, MSCs can unfavorably support tumor progress by a diversity of mechanisms, containing the stimulation of drug resistance, proangiogenic functions, and eliciting metastasis procedure by stimulation of epithelial-mesenchymal transition (EMT) and also enrichments of the cancer stem cell (CSC) niche (139,140). MSC-derived factors are reliable for the listed unwanted effects, affecting the various hallmarks of cancer.…”
Section: Conclusion and Future Prospectmentioning
confidence: 99%
“…Additionally, the immunosuppressive effect of MSC contributes to cancer cells’ escape from the immune system surveillance. Due to their direct action on immune cells, MSCs are capable of inhibiting apoptosis or inhibition of T cell proliferation which results in a decline of immunogenic activity [ 16 ]. Furthermore, MSC has also shown pro-metastatic effects that are mediated via paracrine factors, including TGF-ÎČ, CXCR4, and CCL5; chemokines secreted from MSC [ 10 , 16 , 17 ].…”
Section: Mesenchymal Stroma/stem Cells (Msc) and Cancermentioning
confidence: 99%
“…Due to their direct action on immune cells, MSCs are capable of inhibiting apoptosis or inhibition of T cell proliferation which results in a decline of immunogenic activity [ 16 ]. Furthermore, MSC has also shown pro-metastatic effects that are mediated via paracrine factors, including TGF-ÎČ, CXCR4, and CCL5; chemokines secreted from MSC [ 10 , 16 , 17 ]. Martin et al (2010) revealed that the co-culture of bone marrow-derived MSC with breast cancer resulted in the overexpression of EMT-specific genes and a decrease of mesenchymal to epithelial (MET) genes [ 18 ].…”
Section: Mesenchymal Stroma/stem Cells (Msc) and Cancermentioning
confidence: 99%
“…While the focus of this paper is on the optimization of current NC-based systems in targeting stem cell markers and pathways, alternative CSC applications like CSCs as vehicles of delivery [ 238 , 334 , 335 ] or even infused stem therapy [ 336 ] cannot be dismissed. As such, MSCs in the context of therapeutic carriers are gaining rapid popularity as a strategy to ensure ameliorated side-effects on account of improved biocompatibility [ 332 , 337 ].…”
Section: Current Regimens For Cancer Therapymentioning
confidence: 99%